Literacy Instruction in Nunavut – Initial Findings - Bartlett, A. Katharine (Antistasis, 2022)
The Nunavut Department of Education adopted a new literacy framework during the 2014/2015 school year. The purpose of this research study is to collect the experiences of Nunavut educators about literacy instruction in the bilingual (Inuktut and English) context of Nunavut. The intention is that this will provide insights into the on-going implementation of the literacy framework and inform the implementation of future educational initiatives. To embrace a balanced borrowing of Western and Indigenous research paradigms and methods, grounded theory guided by a theoretical perspective of social constructionism and Inuit Societal Values was selected as the methodology. Data are being collected using a survey, interviews, and talking circles (focus groups). Currently 55 educators have completed the survey and 2 interviews have taken place. This paper will review the data collected to date, discuss emerging themes, and consider next steps.